Improving Communication Access for Children with Incarcerated Parents. (February 2023) - Jensen, Sarah; Pritzl, Kaitlyn; Charles, Pajarita; Kerr, Margaret; Poehlmann, Julie
Sarah Jensen, Kaitlyn Pritzl, Pajarita Charles, Margaret Kerr, and Julie Poehlmann on maintaining kids' carceral connections.